1993
DOI: 10.1021/bi00210a002
|View full text |Cite
|
Sign up to set email alerts
|

NMR structural studies of the tight complex between a trifluoromethyl ketone inhibitor and the 85-kDa human phospholipase A2

Abstract: Arachidonyl trifluoromethyl ketone (AACOCF3) is a slow- and tight-binding inhibitor of the human cytosolic phospholipase A2 (cPLA2) [Street et al. (1993) Biochemistry 32, 5935]. 19F and 13C NMR experiments have been carried out to elucidate the structure of the cPLA2.AACOCF3 complex. One mole of AACOCF3 per mole of enzyme is tightly bound in the active site while excess molar equivalents of the inhibitor associate loosely and nonspecifically with hydrophobic regions of the protein. Incubation of the cPLA2.AACO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 34 publications
2
83
0
5
Order By: Relevance
“…(17). Additionally, it was reported that AACOCF 3 is both a slow and tight binding inhibitor of cPLA 2 that may form a hemiketal enzyme-inhibitor complex (16,18). The reaction mechanism of cPLA 2 thus might be similar to that of serine protease, esterase, or lipase (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…(17). Additionally, it was reported that AACOCF 3 is both a slow and tight binding inhibitor of cPLA 2 that may form a hemiketal enzyme-inhibitor complex (16,18). The reaction mechanism of cPLA 2 thus might be similar to that of serine protease, esterase, or lipase (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…NMR studies show that the carbon chain of AACOCF 3 binds in a hydrophobic pocket and the carbonyl group of AACOCF 3 forms a covalent bond with the serine 228 in the active site, generating a charged hemiketal oxoanion that interacts with a positively charged group of the enzyme Trimble et al, 1993). AACOCF 3 is a 500-fold more potent inhibitor of cPLA 2 than sPLA 2 (Trimble et al, 1993), indicating that it is a more selective inhibitor of cPLA 2 than sPLA 2 . This inhibitor also blocks cyclooxygenase activity (Riendeau et al, 1994).…”
Section: A Arachidonyl Trifluoromethyl Ketonementioning
confidence: 99%
“…Transfer of the fatty acid from both diacyl-and lysophospholipid substrates to acceptors other than water initially suggested the existence of such an acyl-enzyme intermediate (10,11). Further corroboration came when NMR studies indicated the formation of a hemiketal between arachidonyl trifluoromethyl ketone (a potent inhibitor of both activities) and an enzyme hydroxyl group (24). Finally, a serine residue (Ser-228) was identified to be essential for the PLA 2 activity and was also shown to be the site of enzyme acylation (15,25).…”
mentioning
confidence: 97%